THE INFLUENCE OF PERCEPTION OF SECURITY, EASE OF USE, AND HABIT ON QRIS USAGE DECISIONS - Risa; Nuriyah, Aminah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to examine the influence of the perception of security, ease of use, and habits on interest in using QRIS (Quick Response Code Indonesian Standard) in the younger generation in the Greater Jakarta area, Indonesia. QRIS is a digital payment method encouraged by Bank Indonesia to support the national non-cash movement. The research method used was quantitative with data collection through questionnaires distributed to 120 respondents aged 13 to 44 years. Data analysis was carried out using Structural Equation Modeling (SEM) with Partial Least Square (PLS) to test the relationship between variables. The results showed that the perception of security, ease of use, and habits had a significant effect on the interest in using QRIS. These findings provide practical implications for financial institutions and policymakers to increase the adoption of digital payments through improved security, convenience, and habit-building in younger generations. This research also contributes to the fintech literature and digital payment behavior in emerging markets